Respuesta :

f(-4) = 3/(-4)(2)
f(-4)= 3/-8

f(g(1))= 3/(2(1)^3)(2)
f(g(1))= 3/(2)(2)
f(g(1))= 3/4

a. The value of f(-4) is [tex]3 \div -8[/tex]

b. The value of fg(1) is [tex]3\div 4[/tex]

Calculation of the value of f(-4) and fg(1):

Since [tex]F(x)=3\div x\times 2\ and\ g(x)=2\times x\times 3[/tex]

So,

a. The value of f(-4) is

[tex]= 3\div (-4)(2)\\\\= 3\div -8[/tex]

And,

b. The value of fg(1) is

[tex]= 3\div (2(1)^3)(2)\\\\= 3\div (2)(2)\\\\= 3\div 4[/tex]

learn more about the function here: https://brainly.com/question/24309536